2007
DOI: 10.1007/s00421-007-0394-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rest interval length on metabolic responses to the bench press exercise

Abstract: The purpose of this study was to examine the effects of different rest interval (RI) lengths on metabolic responses to the bench press. Eight resistance-trained men performed 10 randomized protocols [five sets of bench press with 75 or 85% of 1RM for ten (10REP) and five repetitions (5REP), respectively, using different RI (30 s, 1, 2, 3, 5 min)]. Oxygen consumption (VO(2)) was measured during exercise and for 30 min post exercise. For 30-s and 1-min RI: reductions (15-55%) in resistance and volume were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
106
2
39

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 39 publications
15
106
2
39
Order By: Relevance
“…The resting VO 2 rate was approximately 0.3 L min −1 for both groups and was multiplied by the rate recovery time to produce the equivalent of rest (0.3 L min −1 × 45 min=13.5 L) using an adopted caloric equivalent (CE) of 4.92 kcal L −1 of oxygen consumed for the calculation of EE in EPOC. For the calculation of EE in the RES, an adopted CE of 5.05 kcal L −1 of VO 2 was used, a value for which there is consensus in the literature due to the large increase in CO 2 production that occurs during the RES due to hyperventilation and thus generating RER values above 1 (Ratamess et al 2007). The values were obtained from the sum of the product of the mean VO 2 per minute by the CE in this recovery period, subtracting the total value of the BMR of the participants or the number of kilocalories that the subjects would have consumed during the period of the RES and EPOC had they not performed the RES (Ratamess et al 2007;Thornton and Potteiger 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resting VO 2 rate was approximately 0.3 L min −1 for both groups and was multiplied by the rate recovery time to produce the equivalent of rest (0.3 L min −1 × 45 min=13.5 L) using an adopted caloric equivalent (CE) of 4.92 kcal L −1 of oxygen consumed for the calculation of EE in EPOC. For the calculation of EE in the RES, an adopted CE of 5.05 kcal L −1 of VO 2 was used, a value for which there is consensus in the literature due to the large increase in CO 2 production that occurs during the RES due to hyperventilation and thus generating RER values above 1 (Ratamess et al 2007). The values were obtained from the sum of the product of the mean VO 2 per minute by the CE in this recovery period, subtracting the total value of the BMR of the participants or the number of kilocalories that the subjects would have consumed during the period of the RES and EPOC had they not performed the RES (Ratamess et al 2007;Thornton and Potteiger 2002).…”
Section: Methodsmentioning
confidence: 99%
“…For the calculation of EE in the RES, an adopted CE of 5.05 kcal L −1 of VO 2 was used, a value for which there is consensus in the literature due to the large increase in CO 2 production that occurs during the RES due to hyperventilation and thus generating RER values above 1 (Ratamess et al 2007). The values were obtained from the sum of the product of the mean VO 2 per minute by the CE in this recovery period, subtracting the total value of the BMR of the participants or the number of kilocalories that the subjects would have consumed during the period of the RES and EPOC had they not performed the RES (Ratamess et al 2007;Thornton and Potteiger 2002). The HVRE and LVRE showed an average VO 2 of 0.74 and 0.67 L min −1 , respectively; RER for EE of 0.88 and 0.89, respectively; RES of 0.42 and 0.34 L min −1 , respectively; and RER of 0.87 and 0.81, respectively, for EPOC.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,9 Previous studies have indicated that Ts and Co responses to resistance exercise are affected by several variables such as intensity, volume, duration, rest periods, and muscle mass involvement. 10,11 It is demonstrated that rest interval period between sets would be an important factor that can be manipulated and effects on work performed in subsequent sets, 12,13 the metabolic 14 and hormonal 15---17 responses to exercise training, and training adaptations. 18---20 However, acute response of Co and Ts to different rest interval is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…A manipulação da ordem dos exercícios pode afetar o VT ao influenciar o número de repetições realizadas 6,23,28,31,33 e diferentes VT vêm sendo associados a respostas agudas distintas [37][38][39] que podem ocasionar adaptações crônicas ao treinamento, dentre elas a hipertrofia 40 , proposição do sistema TS. No entanto, os resultados do presente estudo demostram que não houve diferença no VT pela manipulação da ordem dos exercícios nas SEQ dos TS.…”
Section: Discussionunclassified